Anti-bird-poop photovoltaic panel self-cleaning coating and preparation method thereof

CN119286397BActive Publication Date: 2026-10-27ZHUHAI IRIDIUM NANOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411541508.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2026-10-27
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

长时间累积下来,这些化学成分会逐步破坏光伏板的表面材料,进而影响其整体性能和寿命

Benefits of technology

[0019]1、本发明涂料形成涂层具有出色的疏水疏油效果,涂层以聚硅氧烷材料为主体,并且引入氟材料,极大程度地改善表面的化学组成,降低表面自由能,使其能够具有出色的疏水疏油特性,排斥各类液体污染物,防止其在光伏面板表面的附着;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286397B_ABST
    Figure CN119286397B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a bird excrement-resistant self-cleaning coating for photovoltaic panels, which is prepared by reacting the following raw materials in a solvent: octamethylcyclotetrasiloxane 45-60 parts, tetramethyltris-3-trifluoropropylcyclotetrasiloxane 90-120 parts, tetramethyldihydroxydisiloxane 10-12 parts, heptadecafluorodecyltrimethoxysilane 1-3 parts, octa(3-hydroxy-3-methylbutyl dimethyl siloxane) 70-80 parts, silica aerogel 2-5 parts, nano titanium dioxide 18-20 parts, tetramethylammonium hydroxide 1.5-3 parts, and monohydroxyl-terminated polydimethylsiloxane 45-60 parts. The coating layer has excellent bird excrement resistance, and can remove bird excrement and other pollutants from the surface under the action of gravity, wind blowing or rain washing, thereby keeping the surface of the photovoltaic panel clean for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new materials technology, specifically relating to a self-cleaning coating for bird droppings-resistant photovoltaic panels and its preparation method. Background Technology

[0002] Photovoltaic power generation, as a new type of clean energy, has many advantages over traditional power generation, such as being environmentally friendly, pollution-free, and noise-free, making it a sustainable new energy source that my country has been vigorously developing in recent years. With the increasingly widespread deployment of photovoltaic projects, its application scenarios are no longer limited to plains and urban areas, but are expanding to more diverse geographical environments such as mountainous areas and coastal regions. However, this development of photovoltaic power generation in mountainous and coastal areas has also brought new challenges. Especially in mountainous and forested areas, due to frequent bird activity, bird droppings and other pollutants easily adhere to the surface of photovoltaic panels, thus creating shading. This shading not only reduces the amount of sunlight received by the photovoltaic panels but also directly leads to a decrease in power generation efficiency. More seriously, the chemical components contained in bird droppings can corrode the photovoltaic panels. Over a long period of time, these chemical components will gradually damage the surface materials of the photovoltaic panels, thereby affecting their overall performance and lifespan. Considering the complexity and variability of the mountainous and forested environment, cleaning these pollutants is relatively difficult and requires more manpower, material resources, and time for regular cleaning and maintenance. Therefore, developing a self-cleaning photovoltaic panel coating that can resist corrosion from acidic substances such as bird droppings is particularly important. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide a self-cleaning coating for photovoltaic panels that resists bird droppings and its preparation method, which has excellent effect in preventing bird droppings from adhering.

[0004] The technical solution adopted in this invention is:

[0005] A self-cleaning coating for bird droppings-resistant photovoltaic panels is obtained by reacting the following raw materials in a solvent: 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 10-12 parts of tetramethyldihydroxydisiloxane, 1-3 parts of heptadecafluorodecyltrimethoxysilane, 70-80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane), 2-5 parts of silica aerogel, 18-20 parts of nano-titanium dioxide, 1.5-3 parts of tetramethylammonium hydroxide, and 45-60 parts of monohydroxy-terminated polydimethylsiloxane.

[0006] Preferably, the nano-titanium dioxide is anatase nano-titanium dioxide.

[0007] A method for preparing a self-cleaning coating for bird droppings-resistant photovoltaic panels, comprising the following steps:

[0008] (1) Add 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 10-12 parts of tetramethyldihydroxydisiloxane to the reactor and continuously introduce inert gas into it to remove air and moisture.

[0009] (2) Add 1.5 to 3 parts of tetramethylammonium hydroxide and stir at 75-110℃ until the reaction is complete;

[0010] (3) Dissolve the obtained product in a volatile organic solvent. After the solution separates into layers, discard the unreacted monomer in the lower layer and take the upper layer solution. Remove the solvent by rotary evaporation under negative pressure to obtain fluorinated polysiloxane.

[0011] (4) Disperse 2-5 parts of silica aerogel and 18-20 parts of nano titanium dioxide into anhydrous ethanol. Stir at temperature T1 and slowly add 1-3 parts of heptadecafluorodecyltrimethoxysilane. After the reaction is complete, a nanoparticle dispersion is obtained.

[0012] (5) Add 70-80 parts of fluorinated polysiloxane, octa(3-hydroxy-3-methylbutyldimethylsiloxane) and 45-60 parts of monohydroxy-terminated polydimethylsiloxane obtained in step (3) to the nanoparticle dispersion in step (4), stir at temperature T2, and the reaction is complete to obtain a bird droppings-resistant photovoltaic panel self-cleaning coating.

[0013] After mixing the anti-bird droppings photovoltaic panel self-cleaning coating with the curing agent hexamethylene diisocyanate trimer for 5 minutes until evenly mixed, it can be used as the coating to be sprayed; the curing agent can be any one of hexamethylene diisocyanate trimer, trimethylhexamethylene diisocyanate, isoflurane diisocyanate, tetramethylphenylmethylene diisocyanate, or methylcyclohexyl isocyanate.

[0014] Preferably, the inert gas in step (1) is nitrogen.

[0015] Preferably, the volatile organic solvent in step (3) is ethanol.

[0016] Preferably, the evaporation operation in step (3) is rotary evaporation under negative pressure.

[0017] Preferably, T1 is 25–60°C and T2 is 25–60°C. The purpose of heating is to accelerate the reaction rate.

[0018] The bird-drop-resistant self-cleaning coating for photovoltaic panels provided by this invention has the following beneficial effects:

[0019] 1. The coating formed by the present invention has excellent hydrophobic and oleophobic effects. The coating is mainly composed of polysiloxane material and introduces fluorine material, which greatly improves the chemical composition of the surface and reduces the surface free energy, so that it can have excellent hydrophobic and oleophobic properties, repel various liquid pollutants, and prevent them from adhering to the surface of photovoltaic panels.

[0020] 2. The coating of this invention forms a coating with excellent anti-bird droppings adhesion effect. The good chemical inertness of the fluorosilicone material can prevent various organic substances in liquid bird droppings from forming interaction forces with the coating surface, weakening the adhesion of bird droppings to the surface, allowing them to be removed from the surface by gravity due to the excellent amphoteric properties of the coating. At the same time, the introduction of nano-titanium dioxide can decompose organic pollutants on the surface under sunlight. For small amounts of bird droppings, it can achieve complete degradation, while for large amounts of bird droppings, it can degrade the chemical bonds formed between bird droppings and the coating surface, reducing the adhesion of bird droppings and making them easy to wash off the surface. Nano-titanium dioxide can absorb some ultraviolet rays, preventing coating aging.

[0021] 3. The coating formed by the present invention has excellent self-cleaning effect. When solid contaminants are attached to the surface of the photovoltaic panel, the low polarity composition of the coating surface can reduce the bonding force between the solid contaminants and the coating surface. Under its own gravity, wind or rain washes them off the surface, keeping the photovoltaic panel surface clean for a long time. Attached Figure Description

[0022] Figure 1 The visible light transmittance curves of photovoltaic panel glass coated with the bird droppings-resistant self-cleaning coating obtained in Example 1 of this invention and untreated photovoltaic panel glass.

[0023] Figure 2 A graph showing the anti-bird droppings adhesion performance of the self-cleaning coating for a photovoltaic panel prepared in Example 1 of this invention.

[0024] Figure 3 The degradation rate curve of the bird droppings photodegradation performance test of the bird droppings-resistant self-cleaning coating for photovoltaic panels prepared in Example 1 of this invention.

[0025] Figure 4 The degradation cycle curve of the bird droppings photodegradation performance test of the bird droppings-resistant self-cleaning coating for photovoltaic panels prepared in Example 1 of this invention.

[0026] Figure 5 The comparison curves of power generation efficiency of photovoltaic panels coated with the bird droppings-resistant self-cleaning coating prepared in Example 1 of this invention and untreated photovoltaic panels before and after long-term outdoor placement. Detailed Implementation

[0027] The specific embodiments of the present invention will be described in detail below with reference to specific examples. However, the present invention is not limited to the given embodiments.

[0028] Example 1:

[0029] The specific preparation method of the bird-dropping-resistant self-cleaning coating for photovoltaic panels provided by this invention is as follows:

[0030] (1) Add 50g of octamethylcyclotetrasiloxane, 110g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 12g of tetramethyldihydroxydisiloxane to a reaction flask, continuously purge nitrogen gas into the flask to remove air and moisture, then add 2g of tetramethylammonium hydroxide, heat to 80°C and stir for 6 hours, dissolve the obtained product in ethanol, place it in a separatory funnel, discard the unreacted monomer in the lower layer, take the upper ethanol solution, and remove the ethanol by rotary evaporation under negative pressure to obtain fluorinated polysiloxane;

[0031] (2) Disperse 4 parts of silica aerogel and 19g of nano titanium dioxide into 550g of anhydrous ethanol. After ultrasonic dispersion for 15 minutes, place it under T160℃ and continue stirring for 15 minutes. Then add 2.5g of heptadecafluorodecyltrimethoxysilane dropwise. After the addition is complete, continue the reaction for 2 hours.

[0032] (3) Add the fluorinated polysiloxane, 75g of octa(3-hydroxy-3-methylbutyldimethylsiloxane) POSS and 55g of monohydroxy-terminated polydimethylsiloxane prepared in step (1) to the nanoparticle dispersion in step (2), and continue stirring for 1 hour at T260℃ to obtain the anti-bird droppings photovoltaic panel self-cleaning coating.

[0033] (4) Stir the anti-bird droppings photovoltaic panel self-cleaning coating and the curing agent hexamethylene diisocyanate trimer 85g for 30 minutes until they are evenly mixed, and then it can be used as the coating to be sprayed.

[0034] (5) After rinsing the glass substrate for the photovoltaic panel twice alternately with anhydrous ethanol and deionized water, the coating is sprayed onto the surface of the photovoltaic glass panel while keeping the glass panel horizontal during the spraying process. After curing at room temperature for 2 hours, an anti-bird droppings photovoltaic panel self-cleaning coating is prepared on the surface of the photovoltaic glass panel.

[0035] Example 2

[0036] The difference between this embodiment and Example 1 is that the amount of components added is 45g of octamethylcyclotetrasiloxane, 10g of tetramethyldihydroxydisiloxane, and 90g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane. The heating temperature in step (1) is 75℃, T1 is 25℃, and T2 is 25℃. All other aspects are the same as in Example 1.

[0037] Example 3

[0038] The difference between this embodiment and Example 1 is that the amount of components added is 60g of octamethylcyclotetrasiloxane, 12g of tetramethyldihydroxydisiloxane, and 120g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane. The heating temperature in step (1) is 110℃, T1 is 40℃, and T2 is 40℃. All other aspects are the same as in Example 1.

[0039] Example 4

[0040] The difference between this embodiment and Example 1 is that the amount of components added is 18g of nano-titanium dioxide and 1.5g of tetramethylammonium hydroxide, while all other aspects are the same as in Example 1.

[0041] Example 5

[0042] The difference between this embodiment and Example 1 is that the amount of components added is 20g of nano titanium dioxide and 3g of tetramethylammonium hydroxide, while all other aspects are the same as in Example 1.

[0043] Example 6

[0044] The difference between this embodiment and Example 1 is that the amount of components added is 75g of hexamethylene diisocyanate trimer and 45g of monohydroxy-terminated polydimethylsiloxane. Everything else is the same as in Example 1.

[0045] Example 7

[0046] The difference between this embodiment and Example 1 is that the amount of components added is 100g of hexamethylene diisocyanate trimer and 60g of monohydroxy-terminated polydimethylsiloxane. Everything else is the same as in Example 1.

[0047] Example 8

[0048] The difference between this embodiment and Example 1 is that the amounts of the components added are: 1g of heptadecafluorodecyltrimethoxysilane, 70g of octa(3-hydroxy-3-methylbutyldimethylsiloxane), and 2g of silica aerogel. Everything else is the same as in Example 1.

[0049] Example 9

[0050] The difference between this embodiment and Example 1 is that the amounts of the components added are: 3g of heptadecafluorodecyltrimethoxysilane, 80g of octa(3-hydroxy-3-methylbutyldimethylsiloxane), and 4g of silica aerogel. Everything else is the same as in Example 1.

[0051] The coatings obtained in the embodiments of the present invention were subjected to performance testing as follows:

[0052] Visible light transmittance measurement: The transmittance of the samples (coated glass and untreated glass) to visible light was measured using an Agilent Cary 5000 UV-Vis-NIR spectrophotometer. The test samples measured 7.5 cm × 2.5 cm, and a glass slide of the same size was used as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 300 nm to 800 nm.

[0053] Contact Angle Measurement: The contact angles of water / oil droplets (unless otherwise specified, gasoline, i.e., a mixture of aliphatic and cycloalkanes, was measured on the coating surface using a KRü SSDSA25S optical contact angle analysis system. For contact angle measurements in a stationary state, a water / oil droplet (approximately 10 microliters) was first added to the sample surface using a motor-controlled syringe. Once the droplet stabilized, a side image was captured using a camera, and the static contact angle values ​​of the water / oil droplet on the coating surface were obtained through software fitting and calculation.

[0054] Slip Angle Measurement: The slip angle of water / oil droplets on the coating surface was measured using a KRü SSDSA25S optical contact angle analysis system. For slip angle measurement, a motor-controlled rotatable test platform was used to tilt the sample, and the rotation angle of the platform was displayed in real time on a computer connected to the motor. At the start of the test, the initial tilt angle of the platform was maintained at 0°. After a water / oil droplet (approximately 10 microliters) was added to the coating surface using a syringe, the platform was rotated by the motor. The rotation stopped the instant the droplet began to slide on the surface, and the rotation angle displayed on the computer was recorded as the roll angle. Each sample was measured at three different locations to reduce data error.

[0055] Bird droppings resistance test: The bird droppings resistance test was conducted using an aqueous solution of trypsin to simulate bird droppings. During the test, coated glass substrates and untreated glass substrates were placed at a 20° angle in a forced-air drying oven. Then, 3g of an aqueous solution of trypsin (10wt% trypsin) was added dropwise to the sample surface. After heating to 60°C and standing for three hours, the mass of the deposits on the sample surface was weighed and recorded as the mass of bird droppings on the sample surface. The surface was then rinsed with water, and after the water dried, the mass of the residue on the sample surface was weighed again.

[0056] Bird droppings photodegradation performance test: The bird droppings photodegradation curve of the coated surface was simulated using an aqueous solution of trypsin. During the test, the coated glass substrate was placed horizontally, and 1g of trypsin aqueous solution (10wt% trypsin) was added dropwise to the sample surface. After heating to 60℃ and standing for three hours to dry the moisture, the sample was placed under a 365nm light source, and the sample weight was measured at intervals to calculate the degradation rate. The degradation cycle test was performed by repeating the above operation multiple times and calculating the degradation rate each time to measure the long-term durability of the coating's bird droppings photodegradation performance. If the degradation rate decreased by more than 15 percentage points from the initial degradation rate, it was considered a failure, the test was stopped, and the number of test cycles was recorded.

[0057]

[0058] Coating Adhesion Test: Coating adhesion was tested according to ASTM D3359. All test samples were cross-cut at 1 mm intervals using a QHF cross-cutting tool, then firmly adhered to the marked areas using 3MTM 600 tape. A 2 kg weight was then placed on the tape-attached area and slid down to ensure complete contact between the tape and the test area. After a 90-second pause, the tape was quickly pulled off vertically (90°), and the same area was tested twice. The remaining portion of the coating on the substrate was then observed to assess adhesion. According to the standard, adhesion is rated 5B when the coating peeling is approximately 0%; 4B when the peeling is less than 5%; 3B when the peeling is less than 15%; 2B when the peeling is less than 35%; 1B when the peeling is less than 65%; and 0B when the peeling is greater than 65%.

[0059] Coating abrasion resistance test: The abrasion resistance of the coating was tested using a Taber abrasion tester according to ASTM standard (D4060). A 250-gram load grinding wheel was used during the test. Industries Cs-10 was used as the abrasive medium. First, the coating was sprayed onto a specific annular glass substrate, then fixed to the sample stage of the Taber abrasion tester. Two abrasion wheels were lowered to the left and right sides, adhering tightly to the sample surface. At the start of the test, the sample stage rotated along with the sample; one rotation of the sample was defined as one test cycle. After the test, the abrasion resistance was measured by calculating the changes in the sample's weight loss, transmittance, and anti-wetting properties.

[0060] The formula for calculating the weightlessness rate is as follows:

[0061]

[0062] UV resistance test of coating: The UV resistance of the coating is tested under a UV lamp with a wavelength of 365 nm and a power of 300 W. After the sample is irradiated for a specified time, the changes in the transmittance and anti-wetting properties of the sample are tested to measure the UV resistance.

[0063] Coating weather resistance test: The weather resistance of the coating is tested in a constant temperature and humidity chamber. The chamber is set to 50°C and 95% humidity to simulate a high temperature and high humidity environment. After the sample is placed for a specified time, the changes in the transmittance and anti-wetting properties of the sample are tested to measure the weather resistance.

[0064] Comparative Testing of Photovoltaic Cell Power Generation Efficiency: During the power generation efficiency test, commercially available unencapsulated photovoltaic silicon wafers were selected as the test cells. These were compared with coated glass substrates and untreated glass substrates to assess the impact of coatings on the power generation efficiency of the solar modules. Current density-voltage curves were measured using a Titesys PROVA200A solar cell analyzer. The solar source used in the test was a Yiguangke SOLARBEAM-06-3A sunlight simulator, simulating approximately 100 mW·cm² AM 1.5 sunlight. -2 The intensity of radiation.

[0065] The performance of the coatings formed on the photovoltaic glass panels prepared in each embodiment was tested using the above testing methods. The results are shown in the table below:

[0066]

[0067]

[0068] As shown in the table above, the contact angle of water droplets on the coating surface is greater than 112°, indicating that the coating has excellent hydrophobic properties. Water droplets cannot spread on the surface and can easily slide off the surface at an angle of less than 20°, effectively preventing the formation of water stains on the surface and reducing the loss of transmittance caused by water accumulation on the surface during use. Similarly, the contact angle of oil droplets on the coating surface is greater than 78°, reaching a maximum of 91.39°, with a minimum sliding angle of only 3.31°, indicating that the coating also has excellent oleophobic properties. This can greatly prevent the adhesion of oil contaminants to the surface, keep the photovoltaic panel surface clean, and maintain a high power generation level.

[0069] Based on the data in the table above and Figure 1The comparison curves of the transmittance of photovoltaic panel glass coated with the coating of the present invention and untreated photovoltaic panel glass in the visible light region show that, in the wavelength range of 400-800 nanometers, the transmittance of the coated glass and the untreated glass is not much different, both at the level of about 92% ± 0.5%. The coating of the present invention does not affect the light transmission and can ensure that the photovoltaic panel maintains a high power generation level.

[0070] from Figure 2 The bar chart showing the test results of the anti-bird droppings self-cleaning coating for photovoltaic panels reveals that after drying, the coated glass substrate had approximately 0.064g of trypsin solution residue, while the untreated glass substrate had approximately 0.286g. Almost all the trypsin solution remained on the untreated glass substrate, demonstrating the superior anti-bird droppings adhesion performance of the coating. After rinsing with water, the residue on the coated glass substrate decreased to 0.021g, almost negligible, while the untreated glass substrate still had a high residue of 0.249g. This indicates that even with a small amount of bird droppings adhering to the coating, it can be easily removed by external water flow, reducing the corrosion of the glass material by bird droppings and minimizing irreversible damage to the photovoltaic modules.

[0071] from Figure 3 The degradation rate curves in the photodegradation performance test of bird droppings on the glass surface of the photovoltaic panel coated with the anti-bird droppings photovoltaic panel self-cleaning coating show that the degradation rate of bird droppings simulants gradually increases with the increase of light exposure time. This indicates that the mass of bird droppings simulants on the coating surface gradually decreases under the photocatalytic decomposition of titanium dioxide. This shows that the titanium dioxide filler introduced into the coating can photodegrade organic pollutants on the surface under light irradiation.

[0072] from Figure 4 As can be seen from the degradation cycle test curve, in the 50 bird droppings simulation test on the glass surface of the same anti-bird droppings photovoltaic panel coated with the self-cleaning coating, the degradation efficiency was always maintained at a high level. This shows that the coating has excellent photodegradation durability and can meet the requirements of long-term service of the coating on the photovoltaic panel surface.

[0073] from Figure 5The comparison curves of the power generation efficiency of photovoltaic panels coated with the anti-bird droppings self-cleaning coating and untreated photovoltaic panels before and after long-term outdoor placement show that, initially, the open-circuit voltage and short-circuit current of both are almost equal. This indicates that the coating does not significantly affect the original performance of the photovoltaic panels and can maintain their original power generation efficiency. After 60 days of outdoor placement, the power generation efficiency of the untreated photovoltaic panel showed a significant decrease. This is mainly because the accumulation of pollutants on the photovoltaic panel surface affected light intake, reducing the power generation level of the photovoltaic panel. In contrast, the photovoltaic panel coated with the anti-bird droppings self-cleaning coating only experienced a slight decrease in power generation efficiency even after 60 days. This demonstrates that the coating of this invention has excellent anti-bird droppings adhesion and self-cleaning properties, enabling it to keep the surface of the photovoltaic panel clean in outdoor environments and maintain a high power generation level.

[0074] The present invention has been described in detail above with reference to specific embodiments. However, the present invention is not limited to the contents described above. Various changes made within the scope of knowledge possessed by those skilled in the art, without departing from the inventive concept, still fall within the protection scope of the present invention.

Claims

1. A self-cleaning coating for bird droppings-resistant photovoltaic panels, characterized in that, It is obtained by reacting raw materials including the following components in a solvent: 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 10-12 parts of tetramethyldihydroxydisiloxane, 1-3 parts of heptadecafluorodecyltrimethoxysilane, 70-80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane), 2-5 parts of silica aerogel, 18-20 parts of nano titanium dioxide, 1.5-3 parts of tetramethylammonium hydroxide, and 45-60 parts of monohydroxy-terminated polydimethylsiloxane; It includes the following steps: (1) Add 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 10-12 parts of tetramethyldihydroxydisiloxane to the reactor and continuously introduce inert gas into it to remove air and moisture. (2) Add 1.5 to 3 parts of tetramethylammonium hydroxide and stir at 75-110℃ until the reaction is complete; (3) Dissolve the obtained product in a volatile organic solvent. After the solution separates into layers, discard the unreacted monomer in the lower layer, take the upper layer solution, and remove the solvent by evaporation to obtain fluorinated polysiloxane. (4) Disperse 2-5 parts of silica aerogel and 18-20 parts of nano titanium dioxide in anhydrous ethanol. Stir at 25-60℃ and slowly add 1-3 parts of heptadecafluorodecyltrimethoxysilane. After the reaction is complete, a nanoparticle dispersion is obtained. (5) Add 70-80 parts of fluorinated polysiloxane, octa(3-hydroxy-3-methylbutyldimethylsiloxane) and 45-60 parts of monohydroxy-terminated polydimethylsiloxane obtained in step (3) to the nanoparticle dispersion in step (4), stir at a temperature of 25-60°C until the reaction is complete, and obtain the anti-bird droppings photovoltaic panel self-cleaning coating.

2. The bird-dropping-resistant self-cleaning coating for photovoltaic panels according to claim 1, characterized in that, The nano-titanium dioxide is anatase nano-titanium dioxide.

3. The bird-dropping-resistant self-cleaning coating for photovoltaic panels according to claim 1, characterized in that, The inert gas in step (1) is nitrogen.

4. The bird-dropping-resistant self-cleaning coating for photovoltaic panels according to claim 1, characterized in that, The volatile organic solvent in step (3) is ethanol.

5. The bird-dropping-resistant self-cleaning coating for photovoltaic panels according to claim 1, characterized in that, The evaporation operation in step (3) is rotary evaporation under negative pressure conditions.

Citation Information

Patent Citations

  • Solar photovoltaic panel surface self-cleaning coating and preparation method thereof

    CN114231177A

  • High-wear-resistance water-based elastic coating

    CN118406427A